2010
DOI: 10.1021/jp911125w
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Bulk Heterojunction Solar Cells Based on P3HT and Porphyrin-Modified ZnO Nanorods

Abstract: This work presents hybrid bulk heterojunction solar cells based on dye-sensitized zinc oxide (ZnO) nanorods blended with poly(3-hexylthiophene) (P3HT). Tetra(4-carboxyphenyl)porphyrin (TCPP) molecules were grafted onto the surface of ZnO nanorods to enlarge the absorption spectrum of the blend. We demonstrate that additional bands in the external quantum efficiency (EQE) spectra corresponding to Soret and Q-band absorption can already been observed at very low dye concentration at the ZnO surface. Therefore, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
100
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 35 publications
1
100
1
Order By: Relevance
“…In contrast to our studies using porphyrin grafting at ZnO NRs [21], for which the long-lived decay component was suppressed by the ligand and addressed to reduction of charge trapped at the hybrid interface, grafting of 1 is not affecting the intensity of the second long lived components. It is possible that rather direct interaction between the -conjugated systems with the ZnO surface is involved in the passivation of trap state at the hybrid interface than the carboxylic acid groups used for the grafting of the ligand to the ZnO surface.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our studies using porphyrin grafting at ZnO NRs [21], for which the long-lived decay component was suppressed by the ligand and addressed to reduction of charge trapped at the hybrid interface, grafting of 1 is not affecting the intensity of the second long lived components. It is possible that rather direct interaction between the -conjugated systems with the ZnO surface is involved in the passivation of trap state at the hybrid interface than the carboxylic acid groups used for the grafting of the ligand to the ZnO surface.…”
Section: Resultscontrasting
confidence: 99%
“…Figure 1b shows the molecular structure of 1 as well as a simplified energy diagram of this hybrid solar cell taking into account the energy level of molecule 1 and ZnO [21,30]. It is worth mentioning that ZnO and P3HT as well as 1 form a type II heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, metal oxide nanorods with a diameter less than 20 nm and a length in a range of 100-200 nm might provide an efficient, stable pathway for the transport of photogenerated charge carriers to electrodes as a channel when hybridized into the active layer of polymer-based solar cells. 8 Furthermore, it has been suggested that the dyes grafted at the nanorod surface might also improve the characteristics of light absorption and charge carrier separation when their energy levels are optimized with those of the metal oxides.…”
mentioning
confidence: 99%